Implementation of High Security Cryptographic System with Improved Error Correction and Detection Rate using FPGA - Narendra Babu T; Fazal Noorbasha; Leenendra Chowdary Gunnam (Institute of Advanced Engineering and Science, 2016)
In this article, an encryption algorithm with an error detection technique is presented for highly secured reliable data transmission over unreliable communication channels. In this algorithm, an input data is mapped into orthogonal code first. After that the code is encrypted with the help of Linear Feedback Shift Register (LFSR). The technique has been successfully verified and synthesized using Xilinx by Spartan-3E FPGA. The results show that the error detection rate has been increased to 100% by proposed encryption scheme is effective and improves bandwidth efficiency.